Characterization and thermal performance assessment of earthen adobes and walls additive with different date palm fibers. (December 2021) - Mellaikhafi, Abdellah; Ouakarrouch, Mohamed; Benallel, Abderrahim; Tilioua, Amine; Ettakni, Mahmoud; Babaoui, Abdelhak; Garoum, Mohammed; Alaoui Hamdi, Moulay Ahmed
Abstract: This study deals on the one hand, with experimental characterization of the thermophysical properties of adobes made from raw earth reinforced with five different plant waste fibers from palm trees in the Drâa-Tafilalet region in southeastern Morocco (Pinnate leaves, Palm fiber mesh, Palm trunk, Petiole and Palm cluster) and on the other hand, with numerical simulation based on the one-dimensional numerical model to evaluate the effect of the wall constructed in studied adobe on the heat flux and the thermal comfort of the building. The results of the experimental study show that the thermal properties of the samples improve and are different depending on the type of fibers incorporated. Indeed, the thermal insulation property improves at least by about 30% for a mass fraction of 6% of the petiole and palm fiber mesh and at most 48% for 6% of the pinnate leaf fibers. Moreover, the adobes containing the Pinnate leaf fibers offer the best insulation property compared to those containing the other four fibers with thermal conductivities of about 0.312 W/(m.K) and 0.265 W/(m.K) respectively for the two mass fractions of 3% and 6%, as well as its rate thermal damping of diffusion is maximum due to its low value of thermal diffusivity. Numerical simulation results show a maximum decrease of about 46% of the flux through the walls contained the fibers of pinnate leaves. In addition, the heat flux time lag and the heat flux decrement factor improve, ensuring good energy efficiency.